Postmenopausal women with HIV have increased tooth loss - Sunil Wadhwa; Taylor R. Finn; Karolina Kister; Satoko Matsumura; Michael Levit; Anyelina Cantos; Jayesh Shah; Bruno Bohn; Evanthia Lalla; John T. Grbic; Ryan T. Demmer; Michael T. Yin (BMC, 2024)
Abstract Background With effective antiretroviral therapy, people with HIV (PWH) are living longer and aging; the majority of PWH in the United States are now over the age of 50 and in women have gone through the menopause transition. Menopause potentiates skeletal bone loss at the spine, hip, and radius in PWH. The alveolar bone which surronds the teeth is different than long bones because it is derived from the neural crest. However, few studies have assessed the oral health and alveolar bone in middle aged and older women with HIV. Therefore, the objective of this study was to evaluate periodontal disease and alveolar bone microarchitecture in postmenopausal women with HIV. Methods 135 self-reported postmenopausal women were recruited (59 HIV-, 76 HIV + on combination antiretroviral therapy with virological suppression) from a single academic center. The following parameters were measured: cytokine levels (IFN-γ, TNF-α, IL-1β, IL-2, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12p70, IL-13, IL-17 A, OPG, and RANKL) in gingival crevicular fluid, bleeding on probing, probing depth, clinical attachment loss, number of teeth present, alveolar crestal height, and alveolar bone microarchitecture. Results The mean age of participants was 57.04+/-6.25 years and a greater proportion of women with HIV were black/African American (HIV + 68.42%, HIV- 23.73%; p < 0.001). There was no significant difference in bleeding on probing (p = 0.17) and attachment loss (p = 0.39) between women who were HIV infected vs. HIV uninfected. Women with HIV had significantly higher RANKL expression in Gingival Crevicular Fluid (HIV + 3.80+/-3.19 pg/ul, HIV- 1.29+/-2.14 pg/ul ; p < 0.001), fewer teeth present (HIV + 17.75+/-7.62, HIV- 22.79+/-5.70; p < 0.001), ), lower trabecular number (HIV + 0.08+/-0.01, HIV- 0.09+/-0.02; p = 0.004) and greater trabecular separation (HIV + 9.23+/-3.11, HIV- 7.99+/-3.23; p = 0.04) compared to women without HIV that remained significant in multivariate logistic regression analysis in a sub-cohort after adjusting for age, race/ethnicity, smoking status, and diabetes. Conclusion Postmenopausal women with HIV have deterioration of the alveolar trabecular bone microarchitecture that may contribute to greater tooth loss.